Charisma and fascism in interwar Europe - Pinto, António Costa; Eatwell, Roger; Larsen, Stein Ugelvik (Totalitarian movements and political religions, 2007)
Looks at the leaders of fascism and related movements in the inter-war era. This book shows how fascist leaders came to personify their movements and why the "Fuhreprinzip" was applied in all fascist organizations. It also explains how fascist leadership was of a very particular kind.